Environment-friendly biodegradable waterproof coiled material and preparation method thereof
By adopting a multi-layer structure of environmentally friendly biodegradable waterproof coil, using materials such as bio-based fibers, bio-based polymers and modified polymers, the problems of environmental pollution and performance of traditional waterproof coils are solved, and efficient and environmentally friendly waterproof performance is achieved.
Patent Information
- Application Number
- CN202510053390.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-14
AI Technical Summary
Traditional waterproof coils have problems of environmental pollution and degradation in production and use, especially in the face of extreme weather, their waterproof performance is difficult to meet strict requirements.
Environmentally friendly biodegradable waterproof coils with multi-layer structures include reinforcement layers, waterproof functional layers and surface protective layers. The reinforcement layer uses bio-based fibers and natural fibers, the waterproof functional layer uses bio-based polymers and inorganic fillers, and the surface protective layer uses materials such as modified polyurethane and silicone resin.
It significantly improves the mechanical properties, high temperature resistance, aging resistance and environmental protection characteristics of the waterproof coil, extends the service life of the coil, and reduces environmental pollution.
Smart Images

Figure CN119610800A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waterproof coiled materials, and relates to an environmentally friendly biodegradable waterproof coiled material and a preparation method thereof. Background Art
[0002] Waterproofing membrane is one of the indispensable key materials in the modern construction industry. It is widely used in roofs, basements, tunnels and other parts of buildings that require waterproofing protection. Its main function is to prevent moisture from penetrating into the structural layer of the building, thereby avoiding water damage to the building, protecting the building's infrastructure and internal facilities, and extending the service life of the building. The application range of waterproofing membrane is extremely wide, covering residential buildings, commercial buildings, industrial buildings, infrastructure projects and other fields. Especially in areas facing rainy, humid or wet climates, the role of waterproofing membrane is even more important.
[0003] As global climate change becomes increasingly severe and extreme weather phenomena occur more frequently, the performance requirements for waterproof membranes in buildings have become increasingly stringent. Traditional waterproof materials, such as asphalt waterproof membranes, synthetic rubber waterproof membranes, and polyvinyl chloride waterproof membranes, have good waterproof effects, but they often rely on petroleum-based polymers as raw materials. Such materials often consume a lot of energy during the production process and release greenhouse gases and harmful substances, resulting in a large environmental burden. In addition, petroleum-based materials may gradually age during use due to external factors such as ultraviolet rays, oxidation, and temperature changes, resulting in a decrease in waterproof performance or even failure. Therefore, the use of traditional waterproof membranes not only poses environmental pollution problems, but may also affect the long-term use effect and sustainability of buildings.
[0004] Therefore, it is necessary to develop an environmentally friendly biodegradable waterproof membrane to make up for the shortcomings of traditional waterproof membranes. Summary of the invention
[0005] In view of the above problems, the object of the present invention is to provide an environmentally friendly biodegradable waterproofing membrane and a preparation method thereof. The environmentally friendly biodegradable waterproofing membrane comprises multiple functional layers, and provides excellent mechanical properties and environmental protection characteristics by adopting a reinforcement layer of high-toughness, bio-based fibers and natural fibers. The waterproofing functional layer uses a combination of renewable bio-based polymers and inorganic fillers to significantly improve the waterproofing performance, high temperature resistance and aging resistance. The surface protective layer enhances the hydrophobicity, anti-pollution, heat resistance and UV resistance by combining modified polyurethane, fluorinated polyurethane and silicone resin.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an environmentally friendly biodegradable waterproof roll material, the environmentally friendly biodegradable waterproof roll material comprising a reinforcement layer, a waterproof functional layer and a surface protection layer; wherein the reinforcement layer, the waterproof functional layer and the surface protection layer are stacked in sequence;
[0008] The reinforcement layer includes bio-based fibers, natural fibers, a binder, and a hydrophobic modifier;
[0009] The waterproof functional layer comprises a bio-based polymer, modified silica nanoparticles, a modified filler, a toughening agent and an antioxidant;
[0010] The surface protection layer comprises fluorinated polyurethane, silicone resin, fatty acid-coated reflective material, antioxidant, ultraviolet absorber and hydrophobic modifier.
[0011] Bio-based fibers and natural fibers are selected as the main materials in the reinforcement layer: bio-based fibers have high toughness and degradability, while natural fibers provide excellent strength and tolerance. Through shearing, the fibers are processed into short fibers with a large specific surface area, which not only helps to disperse evenly in the solution later, but also significantly improves the wetting effect of the binder. The pretreated fibers provide a reliable mechanical performance foundation for the formation of the reinforcement layer, and can serve as a high-strength and durable base for the coil, significantly improving the tear resistance and deformation resistance of the coil, while giving the coil environmental protection and degradability.
[0012] After the binder is dispersed in water, its active functional groups (such as hydroxyl and carboxyl) are partially dissociated, which enhances the chemical activity and provides reaction sites for the subsequent bonding between fibers. Through cross-linking, the binder can not only significantly improve the tensile strength and deformation resistance of the reinforcement layer, but also improve the stability of its overall structure, providing solid support for the waterproof functional layer and surface protection layer.
[0013] In the process of combining with the fiber, the binder forms a preliminary adhesion layer through hydrogen bonding, van der Waals force or covalent bonding (such as the reaction of carboxyl groups with hydroxyl groups on the fiber surface). Subsequently, the long-chain alkyl or fluorinated group in the hydrophobic modifier covers the fiber surface through physical adsorption or chemical bonding, enhancing its hydrophobic properties, thereby giving the reinforcement layer preliminary waterproof properties.
[0014] Under the conditions of high temperature and high pressure, the binder undergoes further cross-linking reaction, significantly improving the bonding force between the fibers; the hydrophobic modifier solidifies at high temperature, enhancing its adhesion on the fiber surface and improving the overall hydrophobic performance of the reinforcement layer. After hot pressing, the reinforcement layer forms a fiber network structure with high strength and good density. This structure not only provides a solid base for the waterproof membrane, but also effectively carries the waterproof functional layer and surface protection layer, playing an important role in resisting external mechanical stress and environmental erosion, thereby significantly extending the service life of the membrane.
[0015] Bio-based polymers are used as base materials in the waterproof functional layer. Bio-based polymers are derived from natural resources, are renewable and abundant, and their production process is more sustainable than petroleum-based polymers. Secondly, bio-based polymers usually have good flexibility, which helps the roll material adapt to the shape and condition of various substrate surfaces during laying. At the same time, the polar groups in the bio-based polymers are easy to combine with the surface groups of inorganic fillers (such as silica nanoparticles and montmorillonite) to form a tight interface structure, which significantly improves the dispersion of the fillers and the mechanical properties of the materials. During the thermal curing process, bio-based polymers can form a dense network structure through cross-linking reactions between molecular chains, thereby improving the performance of the waterproof functional layer.
[0016] Montmorillonite, bentonite and regenerated cellulose are introduced as fillers in the waterproof functional layer. Montmorillonite is a layered silicate mineral, formed by alternating layers of silicon-oxygen tetrahedrons and aluminum-oxygen octahedrons, with a high specific surface area and nanometer size. Its layered structure can extend the penetration path of water molecules or other substances, thereby improving the barrier performance of the waterproof functional layer; at the same time, montmorillonite has excellent heat resistance, and its structural stability enables it to maintain physical and chemical properties at high temperatures, enhancing the high temperature resistance of the waterproof functional layer. Bentonite also has a similar layered structure, but its interlayer distance is larger, its adsorption capacity is stronger, and it can expand to several times its original volume after absorbing water, further blocking the penetration of water molecules and other substances.
[0017] Montmorillonite and bentonite are modified using bio-based cationic surfactants. Bio-based cationic surfactants replace the cations between the layers of montmorillonite and bentonite through ion exchange, changing the properties of their interlayer structure. At the same time, the long-chain groups form a hydrophobic barrier between the layers or on the surface, thereby enhancing the waterproof performance.
[0018] Regenerated cellulose is a highly uniform linear polymer material processed from natural cellulose. It has high crystallinity and is rich in hydroxyl groups on the surface. Its hydroxyl groups stabilize the dispersion of fillers in the matrix by hydrogen bonding with the surface of montmorillonite and bentonite. In addition, the fibrous morphology of regenerated cellulose forms a physical intercalation with the polymer matrix, which helps to improve the density of the waterproof layer and reduce the formation of micropores and cracks, thereby improving the waterproof performance.
[0019] There is also a synergistic effect between the three: the layered structure of montmorillonite and bentonite significantly extends the water penetration path, and regenerated cellulose reduces the water diffusion channel through a dense network structure. The three work together to improve the waterproof performance; secondly, montmorillonite and bentonite provide nano-enhancement, and regenerated cellulose forms a fiber network and interface bonding, which comprehensively improves the tensile strength and toughness of the waterproof functional layer; in addition, the thermal stability of montmorillonite and bentonite itself, coupled with the semi-crystalline structure of regenerated cellulose, can improve the high temperature resistance of the waterproof layer. The synergistic effect of the three improves the anti-aging, environmental corrosion resistance and overall service life of the waterproof functional layer, providing high-performance guarantee for the waterproof membrane.
[0020] The present invention limits the weight of the modified filler to 20-30 parts. When the amount of modified filler added is too much, the viscosity of the system will be too high, affecting the processing performance, and the filler and the polymer matrix interface will be poorly bonded, thereby reducing the overall strength and toughness, resulting in increased brittleness and easy cracking of the coil; when the amount added is too little, the hydrophobicity and weather resistance of the functional layer will decrease, resulting in insufficient performance of the coil.
[0021] The present invention introduces silicon dioxide nanoparticles into the waterproof functional layer, and the nanometer or micrometer size forms a multi-level rough structure on the surface of the waterproof functional layer. The rough structure is combined with the long-chain alkyl introduced by stearic acid modification, which significantly reduces the free energy of the silicon dioxide surface, thereby giving the waterproof functional layer super-hydrophobic characteristics and further improving the waterproof performance; in the polymer network, silicon dioxide can also bridge microcracks and pores, inhibit crack expansion, and improve the waterproof layer's ability to resist mechanical damage; at the same time, the high thermal stability and thermal decomposition resistance of silicon dioxide enable the waterproof functional layer to maintain structural stability at high temperatures, reducing performance degradation caused by thermal decomposition; in addition, silicon dioxide itself has a certain absorption and shielding effect on ultraviolet rays, which can slow down the aging problem of the waterproof functional layer caused by ultraviolet radiation and extend its service life.
[0022] The present invention limits the weight of modified silica nanoparticles to 8-15 parts, which are usually used as reinforcing agents and hydrophobic additives to improve the mechanical properties, hydrophobicity and weather resistance of the functional layer. However, when the amount of modified silica nanoparticles added is too much, they are easily dispersed unevenly, increasing the local stress concentration phenomenon, thereby causing the flexibility of the functional layer to decrease, causing the coil to crack easily, and affecting the service life; when the amount of modified silica nanoparticles added is too little, the mechanical strength and hydrophobicity of the waterproof layer may be reduced, resulting in an increased risk of water penetration, and the weather resistance deteriorates, which shortens the service life of the coil.
[0023] In the surface protection layer, perfluorooctyltriethoxysilane is a fluorine-containing silane coupling agent. Its triethoxysilane group is hydrolyzed to form silanol, which is then partially condensed to form oligosiloxane, forming a siloxane network on the surface of the substrate while retaining the fluorocarbon chain. Its surface energy gives the material excellent hydrophobic and protective properties; polyurethane prepolymer is the basis of the film-forming material. By introducing a fluorine-containing silane solution, the silanol or oligosiloxane group may chemically react with the functional groups in the polyurethane to enhance the bonding strength, while retaining the fluorocarbon chain to provide hydrophobicity and anti-pollution properties, providing excellent performance for the surface protection layer.
[0024] Fluorinated polyurethane and silicone resin are introduced at the same time. Fluorinated polyurethane provides hydrophobicity through its low surface energy and improves the flexibility of the protective layer through the flexible part of the molecular structure. Silicone resin has excellent heat resistance and UV resistance due to its unique Si-O bond structure, and can resist oxidation and degradation caused by ultraviolet rays. The mixture of the two forms a composite coating basis with complementary properties.
[0025] Introducing reflective materials into the surface protective layer: Zirconia can effectively reflect and refract visible light and ultraviolet light through its high refractive index, thus improving the light reflectivity of the coating; Titanium dioxide can significantly reduce aging caused by ultraviolet rays with its extremely high refractive index and ultraviolet shielding ability; Zinc oxide further enhances weather resistance by absorbing and scattering ultraviolet rays at the same time. The introduction of these reflective materials can work synergistically, effectively improving the weather resistance of the surface protective layer and extending the service life of the waterproof membrane.
[0026] Palmitic acid is used to modify the reflective material. Palmitic acid is a saturated fatty acid. The carboxyl group in its molecule may interact with the surface of the reflective material through physical adsorption or chemical bonding to form a stable organic coating layer. The long-chain alkyl group of the modified palmitic acid forms a low surface energy structure on the surface, which significantly enhances the hydrophobicity of the reflective material. At the same time, the photocatalytic activity of titanium dioxide under ultraviolet light will accelerate the degradation of the surrounding matrix, and the palmitic acid coating inhibits the photocatalytic reaction by isolating the active sites, thereby effectively extending the life of the coating.
[0027] In a second aspect, the present invention provides a method for preparing an environmentally friendly biodegradable waterproof membrane, the method for preparing the environmentally friendly biodegradable waterproof membrane comprising:
[0028] S1: The bio-based fiber and the natural fiber are sheared, washed and dried to obtain pretreated fiber; the binder is dispersed in deionized water to obtain a binder solution; the pretreated fiber is added to the binder solution to obtain a mixed solution A, a hydrophobic modifier is added after stirring to obtain a mixed solution B, ultrasonically dispersed and stirred to obtain a slurry, the slurry is poured onto a forming mesh of a wet papermaking equipment, a vacuum filtration device is used to form a wet fiber web, the wet fiber web is placed in a hot press to obtain a preliminary reinforcement layer, and the reinforcement layer is obtained after drying;
[0029] S2: dispersing montmorillonite and bentonite in a bio-based cationic surfactant solution, stirring for reaction, filtering, washing and drying after the reaction to obtain a modified mixed filler, adding the modified mixed filler to a regenerated cellulose solution, then adding polyvinyl pyrrolidone, ultrasonically dispersing to obtain a filler mixed solution, and freeze-drying to obtain a modified filler;
[0030] The silica nanoparticles are dispersed in ethanol and stirred to obtain a silica nanoparticle dispersion, stearic acid is added thereto, reacted at a constant temperature, and then filtered, washed, and dried to obtain modified silica nanoparticles;
[0031] The bio-based polymer and the modified silica nanoparticles are mixed under stirring, and then a modified filler, a toughening agent, and an antioxidant are added and stirred to obtain a waterproof functional layer substrate, which is added to a twin-screw extruder for melt blending, and the obtained melt blend is cast into a film and then subjected to heat curing treatment to obtain a waterproof functional layer;
[0032] S3: dispersing perfluorooctyltriethoxysilane in anhydrous ethanol, adding deionized water, dropping acetic acid to adjust the pH, stirring to obtain a fluorinated silane solution; dispersing a polyurethane prepolymer in anhydrous toluene, dropping the fluorinated silane solution, adding triethylamine, reacting at a constant temperature to obtain a reaction solution C, and rotary evaporating to obtain a modified polyurethane;
[0033] Dissolving palmitic acid in anhydrous ethanol to obtain a palmitic acid solution, adding a reflective material to the palmitic acid solution, stirring for reaction, filtering, washing, and drying to obtain a fatty acid-coated reflective material;
[0034] The fluorinated polyurethane and the silicone resin are mixed, stirred and mixed, and then a fatty acid-coated reflective material, an ultraviolet absorber, and a hydrophobic modifier are added in sequence and stirred and mixed to obtain a surface protective layer coating;
[0035] S4: Clean the contact surfaces of the reinforcement layer and the waterproof functional layer, stack them, place them in a hot press for compounding, keep them in the pressed state and naturally cool them to room temperature to obtain a composite material, apply a surface protective layer coating on the surface of the waterproof functional layer, and bake and cure them to obtain an environmentally friendly biodegradable waterproof membrane.
[0036] As a preferred technical solution of the present invention, in step S1, the concentration of the binder is 0.1-0.2 g / mL, for example, it can be 0.1 g / mL, 0.11 g / mL, 0.12 g / mL, 0.13 g / mL, 0.14 g / mL, 0.15 g / mL, 0.16 g / mL, 0.17 g / mL, 0.18 g / mL, 0.19 g / mL or 0.2 g / mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] As a preferred technical solution of the present invention, in step S2, the mass ratio of montmorillonite to bentonite is (1-2):1, for example, it can be 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2.0:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional examples, the mass fraction of the bio-based cationic surfactant solution is 2-5wt.%, for example, it can be 2.0wt.%, 2.2wt.%, 2.4wt.%, 2.6wt.%, 2.8wt.%, 3.0wt.%, 3.2wt.%, 3.4wt.%, 3.6wt.%, 3.8wt.%, 4.0wt.%, 4.2wt.%, 4.4wt.%, 4.6wt.%, 4.8wt.% or 5.0wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional examples, the total mass ratio of the bio-based cationic surfactant to montmorillonite and bentonite is 1:(15-25), for example, it can be 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24 or 1:25, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional examples, the mass ratio of the modified mixed filler to the regenerated cellulose is (5-10):1, for example, it can be 5.0:1, 5.5:1, 6.0:1, 6.5:1, 7.0:1, 7.5:1, 8.0:1, 8.5:1, 9.0:1, 9.5:1 or 10.0:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional examples, the mass fraction of the regenerated cellulose solution is 5-10wt.%, for example, it can be 5.0wt.%, 5.5wt.%, 6.0wt.%, 6.5wt.%, 7.0wt.%, 7.5wt.%, 8.0wt.%, 8.5wt.%, 9.0wt.%, 9.5wt.% or 10.0wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some optional examples, the feeding amount of polyvinyl pyrrolidone accounts for 2-5wt.% of the regenerated cellulose, for example, it can be 2.0wt.%, 2.2wt.%, 2.4wt.%, 2.6wt.%, 2.8wt.%, 3.0wt.%, 3.2wt.%, 3.4wt.%, 3.6wt.%, 3.8wt.%, 4.0wt.%, 4.2wt.%, 4.4wt.%, 4.6wt.%, 4.8wt.% or 5.0wt.%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] In some optional examples, the mass ratio of the silica nanoparticles to stearic acid is (10-20):1, for example, it can be 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1 or 20:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In some optional examples, the mass fraction of the stearic acid ethanol solution is 1-5wt.%, for example, it can be 1.0wt.%, 1.5wt.%, 2.0wt.%, 2.5wt.%, 3.0wt.%, 3.5wt.%, 4.0wt.%, 4.5wt.% or 5.0wt.%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] As a preferred technical solution of the present invention, in step S3, the mass ratio of perfluorooctyltriethoxysilane to polyurethane prepolymer is 1:(5-10), for example, it can be 1:5.0, 1:5.5, 1:6.0, 1:6.5, 1:7.0, 1:7.5, 1:8.0, 1:8.5, 1:9.0, 1:9.5 or 1:10.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the concentration of the palmitic acid solution is 0.1-0.5 mol / L, for example, it can be 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L or 0.5 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional instances, the mass ratio of the reflective material to the palmitic acid solution is 1:(10-20), for example, it can be 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] As a preferred technical solution of the present invention, in step S4, the temperature at which the reinforcing layer and the waterproof functional layer are compounded in a hot press is 150-180°C, for example, it can be 150°C, 152°C, 154°C, 156°C, 158°C, 160°C, 162°C, 164°C, 166°C, 168°C, 170°C, 172°C, 174°C, 176°C, 178°C or 180°C, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0049] In some optional instances, the pressure at which the reinforcing layer and the waterproof functional layer are compounded in a hot press is 5-10 MPa, for example, 5.0 MPa, 5.5 MPa, 6.0 MPa, 6.5 MPa, 7.0 MPa, 7.5 MPa, 8.0 MPa, 8.5 MPa, 9.0 MPa, 9.5 MPa or 10.0 MPa, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] In some optional examples, the time for compounding the reinforcement layer and the waterproof functional layer in the hot press is 10-20 minutes, for example, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional examples, the baking and curing temperature is 80-100°C, for example, it can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In some optional instances, the baking and curing time is 20-30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] As a preferred technical solution of the present invention, the reinforcing layer comprises the following components in parts by weight:
[0054]
[0055] In some optional examples, the mass proportion of bio-based fibers is 40-50 parts, for example, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts or 50 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In some optional examples, the mass proportion of natural fiber is 30-40 parts, for example, it can be 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional examples, the mass proportion of the binder is 15-25 parts, for example, it can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional examples, the mass fraction of the hydrophobic modifier is 5-10 parts, for example, it can be 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.5 parts, 9.0 parts, 9.5 parts or 10.0 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] As a preferred technical solution of the present invention, the waterproof functional layer comprises the following components in parts by weight:
[0060]
[0061]
[0062] In some optional examples, the mass fraction of the bio-based polymer is 60-80 parts, for example, it can be 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts or 80 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some optional examples, the mass fraction of modified silica nanoparticles is 8-15 parts, for example, it can be 8.0 parts, 8.5 parts, 9.0 parts, 9.5 parts, 10.0 parts, 10.5 parts, 11.0 parts, 11.5 parts, 12.0 parts, 12.5 parts, 13.0 parts, 13.5 parts, 14.0 parts, 14.5 parts or 15.0 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In some optional examples, the mass proportion of the modified filler is 20-30 parts, for example, it can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] In some optional examples, the mass proportion of the toughening agent is 1-5 parts, for example, it can be 1.0 parts, 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts or 5.0 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In some optional examples, the weight percentage of the antioxidant is 1-3 parts, for example, it can be 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2.0 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts or 3.0 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] As a preferred technical solution of the present invention, the surface protective layer comprises the following components in parts by weight:
[0068]
[0069] In some optional examples, the mass parts of fluorinated polyurethane are 40-60 parts, for example, it can be 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts or 60 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] In some optional examples, the mass parts of the silicone resin are 10-30 parts, for example, it can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] In some optional examples, the mass proportion of the fatty acid-coated reflective material is 5-20 parts, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 parts, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0072] In some optional examples, the weight proportion of the antioxidant is 0.5-2 parts, for example, it can be 0.5 parts, 0.6 parts, 0.8 parts, 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts or 2.0 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] In some optional examples, the mass fraction of the ultraviolet absorber is 0.5-2 parts, for example, it can be 0.5 parts, 0.6 parts, 0.8 parts, 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts or 2.0 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] In some optional examples, the mass fraction of the hydrophobic modifier is 0.5-2 parts, for example, it can be 0.5 parts, 0.6 parts, 0.8 parts, 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts or 2.0 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] Compared with the prior art, the present invention has the following beneficial effects:
[0076] (1) Bio-based fibers with high toughness and degradability and natural fibers with good strength and tolerance are selected as the main materials in the reinforcement layer, which provides a reliable mechanical performance foundation for the reinforcement layer and gives the coil environmental protection and degradability.
[0077] (2) The use of renewable and flexible bio-based polymers as the base material for the waterproof functional layer not only makes the production process more sustainable but also helps the membrane adapt to various substrate surface conditions during the laying process. Secondly, the polar groups in the bio-based polymers are easy to combine with inorganic fillers to form a tight interface structure, thereby improving the mechanical properties of the material. Moreover, during the thermal curing process, the bio-based polymers can also form a dense network structure through cross-linking reactions between molecular chains, thereby enhancing the performance of the waterproof functional layer.
[0078] (3) Montmorillonite, bentonite and regenerated cellulose are introduced as fillers in the waterproof functional layer: the layered structure of montmorillonite and bentonite significantly prolongs the water penetration path, and the dense network structure of regenerated cellulose reduces the water diffusion channel. The three work together to improve the waterproof performance; in addition, the thermal stability of montmorillonite and bentonite, coupled with the semi-crystalline structure of regenerated cellulose, can improve the high temperature resistance of the waterproof layer. The synergistic effect of the three improves the anti-aging, environmental corrosion resistance and overall service life of the waterproof functional layer, providing high performance guarantee for the waterproof membrane.
[0079] (4) Perfluorooctyl triethoxysilane is used to modify polyurethane in the surface protective layer. By introducing a fluorinated silane solution, silanol or oligosiloxane groups may chemically react with the functional groups in the polyurethane to enhance the bonding strength, while retaining the fluorocarbon chain to provide hydrophobicity and anti-fouling properties, providing excellent performance for the surface protective layer.
[0080] (5) Fluorinated polyurethane and silicone resin are introduced at the same time. Fluorinated polyurethane provides hydrophobicity through its low surface energy and improves the flexibility of the protective layer through the flexible part of its molecular structure. Silicone resin has excellent heat resistance and UV resistance due to its unique Si-O bond structure, and can resist oxidation and degradation caused by ultraviolet rays. The mixture of the two forms a composite coating basis with complementary properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] Figure 1 A flow chart of a method for preparing an environmentally friendly biodegradable waterproof membrane provided in Example 1 of the present invention;
[0082] Figure 2 This is a schematic structural diagram of the environmentally friendly biodegradable waterproof membrane provided by the present invention.
[0083] Reference numerals: 1. substrate; 2. reinforcing layer; 3. waterproof functional layer; 4. surface protection layer. DETAILED DESCRIPTION
[0084] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0085] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products.
[0086] Example 1
[0087] like Figure 1 As shown, this embodiment provides an environmentally friendly biodegradable waterproof membrane and a preparation method thereof, and the preparation method specifically comprises the following steps:
[0088] S1: Pre-treating the bio-based fiber and the natural fiber and dispersing them in a binder solution to obtain a mixed solution A, adding a hydrophobic modifier to obtain a mixed solution B, ultrasonically dispersing and stirring to obtain a slurry, and obtaining a reinforcement layer through a wet molding process;
[0089] Specifically, S1: 45 parts of polylactic acid fibers and 30 parts of flax fibers were sheared, washed, and dried to obtain pretreated fibers; 20 parts of polyvinyl alcohol were dispersed in deionized water to obtain a polyvinyl alcohol solution with a concentration of 0.1 g / mL; the pretreated fibers were added to the polyvinyl alcohol solution to obtain a mixed solution A, and 8 parts of stearic acid were added to obtain a mixed solution B after stirring the mixture at a stirring speed of 800 rpm for 20 min, and ultrasonic dispersion and stirring were performed to obtain a slurry, wherein the ultrasonic dispersion power was 250 W, the time was 10 min, the stirring temperature was 45° C., and the time was 15 min, the slurry was poured onto a forming mesh of a wet papermaking equipment, a vacuum filtration device was used to form a wet fiber web, and the web was placed in a hot press to obtain a preliminary reinforcement layer, wherein the hot pressing temperature was 165° C., the pressure was 8 MPa, and the time was 12 min, and the reinforcement layer 2 was obtained after drying;
[0090] S2: dispersing montmorillonite and bentonite in a bio-based cationic surfactant solution to obtain a modified mixed filler, adding the mixed filler to a regenerated cellulose solution, and adding polyvinyl pyrrolidone to obtain a modified filler; dispersing silica nanoparticles in a stearic acid ethanol solution to obtain modified silica nanoparticles;
[0091] The bio-based polymer, modified silica nanoparticles, modified fillers, toughening agents, and antioxidants are mixed, melt-blended, cast, and then thermally cured to obtain a waterproof functional layer;
[0092] Specifically, S2: dispersing montmorillonite and bentonite in a betaine solution with a mass fraction of 2wt.% at a mass ratio of 1:1, wherein the total mass ratio of betaine to montmorillonite and bentonite is 1:20, stirring and reacting at 55°C for 25 minutes, filtering, washing and drying after the reaction to obtain a modified mixed filler, adding the modified mixed filler to a regenerated cellulose solution with a mass fraction of 7.5wt.%, wherein the mass ratio of the modified mixed filler to the regenerated cellulose is 5:1, and then adding polyvinyl pyrrolidone in an amount of 3.4wt.% of the regenerated cellulose, ultrasonically dispersing to obtain a filler mixed solution, and freeze-drying to obtain a modified filler;
[0093] The silica nanoparticles are dispersed in ethanol and stirred to obtain a silica nanoparticle dispersion, stearic acid is added thereto, wherein the mass fraction of stearic acid in ethanol is 1 wt.%, and the mass ratio of the silica nanoparticles to stearic acid is 10:1, and the reaction is carried out at a constant temperature of 75° C. for 3 hours, and then filtered, washed, and dried to obtain modified silica nanoparticles;
[0094] 70 parts of polylactic acid, polybutylene succinate and 10 parts of modified silica nanoparticles were mixed under stirring, and then 25 parts of modified filler, 3 parts of glycerol and 2.5 parts of vitamin E were added and stirred to obtain a waterproof functional layer substrate, which was added to a twin-screw extruder for melt blending, wherein the melt blending temperature was 182° C., the time was 15 min, and the screw speed was 180 rpm. The obtained melt blend was cast into a film and then heat-cured to obtain a waterproof functional layer 3;
[0095] S3: using perfluorooctyl triethoxysilane to modify a polyurethane prepolymer to obtain a modified polyurethane; using palmitic acid to modify a reflective material to obtain a fatty acid-coated reflective material; mixing a fluorinated polyurethane and an organic silicone resin, and then sequentially adding a fatty acid-coated reflective material, an ultraviolet absorber, and a hydrophobic modifier and mixing them evenly to obtain a surface protective layer coating;
[0096] Specifically, S3: dispersing perfluorooctyl triethoxysilane in anhydrous ethanol with a mass fraction of 8 wt.%, adding deionized water, wherein the mass ratio of anhydrous ethanol to deionized water is 90:10, adding acetic acid to adjust the pH to 4, stirring to obtain a fluorinated silane solution; dispersing a polyurethane prepolymer in anhydrous toluene, wherein the mass fraction of the polyurethane prepolymer in anhydrous ethanol is 12.5 wt.%, adding a fluorinated silane solution, wherein the mass ratio of perfluorooctyl triethoxysilane to the polyurethane prepolymer is 1:8, adding triethylamine in a molar ratio of 1:1 to perfluorooctyl triethoxysilane, reacting at a constant temperature of 65°C for 1.5 hours to obtain a reaction solution C, and rotary evaporating to obtain a modified polyurethane;
[0097] Dissolve palmitic acid in anhydrous ethanol to obtain a palmitic acid solution with a concentration of 0.25 mol / L, add zirconium oxide to the palmitic acid solution, wherein the mass ratio of zirconium oxide to the palmitic acid solution is 1:20, stir and react at 54° C. for 3.4 h, filter, wash, and dry to obtain a fatty acid-coated reflective material;
[0098] 50 parts of fluorinated polyurethane and 22 parts of silicone resin were mixed, and 10 parts of fatty acid coated reflective material, 1 part of vitamin E, 1.5 parts of ultraviolet absorber UV-326, and 2.2 parts of stearic acid were added in sequence and stirred to obtain a surface protective layer coating 4;
[0099] S4: Clean the contact surfaces of the reinforcement layer 2 and the waterproof functional layer 3, and then stack them and place them in a hot press for compounding. The temperature of the hot press compounding is 165°C, the pressure is 7MPa, and the time is 15min. After completion, the pressed state is maintained and naturally cooled to room temperature to obtain a composite material. The surface protective layer coating 4 is coated on the surface 3 of the waterproof functional layer, and baked and cured at 90°C for 25min to obtain an environmentally friendly biodegradable waterproof membrane, such as Figure 2 shown.
[0100] Example 2
[0101] This embodiment provides an environmentally friendly biodegradable waterproof coiled material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0102] S1: Pre-treating the bio-based fiber and the natural fiber and dispersing them in a binder solution to obtain a mixed solution A, adding a hydrophobic modifier to obtain a mixed solution B, ultrasonically dispersing and stirring to obtain a slurry, and obtaining a reinforcement layer through a wet molding process;
[0103] Specifically, S1: 40 parts of polyhydroxy fatty acid fibers and 40 parts of bamboo fibers were sheared, washed, and dried to obtain pretreated fibers; 25 parts of starch glue were dispersed in deionized water to obtain a starch glue solution with a concentration of 0.15 g / mL; the pretreated fibers were added to the starch glue solution to obtain a mixed solution A, and 5 parts of sodium stearate were added after stirring the mixture at a stirring speed of 900 rpm for 15 min to obtain a mixed solution B, and ultrasonically dispersed and stirred to obtain a slurry, wherein the ultrasonic dispersion power was 200 W, the time was 15 min, the stirring temperature was 40° C., and the time was 10 min, the slurry was poured onto a forming mesh cloth of a wet papermaking equipment, a vacuum filtration device was used to form a wet fiber web, and the web was placed in a hot press to obtain a preliminary reinforcement layer, wherein the hot pressing temperature was 180° C., the pressure was 5 MPa, and the time was 15 min, and the reinforcement layer 2 was obtained after drying;
[0104] S2: dispersing montmorillonite and bentonite in a bio-based cationic surfactant solution to obtain a modified mixed filler, adding the mixed filler to a regenerated cellulose solution, and adding polyvinyl pyrrolidone to obtain a modified filler; dispersing silica nanoparticles in a stearic acid ethanol solution to obtain modified silica nanoparticles;
[0105] The bio-based polymer, modified silica nanoparticles, modified fillers, toughening agents, and antioxidants are mixed, melt-blended, cast, and then thermally cured to obtain a waterproof functional layer;
[0106] Specifically, S2: dispersing montmorillonite and bentonite in a mass ratio of 1.5:1 in a 5wt.% lauramide propyl betaine solution, wherein the total mass ratio of lauramide propyl betaine to montmorillonite and bentonite is 1:15, stirring and reacting at 50°C for 30 minutes, filtering, washing and drying after the reaction to obtain a modified mixed filler, adding the modified mixed filler to a 5wt.% regenerated cellulose solution, wherein the mass ratio of the modified mixed filler to the regenerated cellulose is 8:1, and then adding polyvinyl pyrrolidone in an amount of 2wt.% of the regenerated cellulose, ultrasonically dispersing to obtain a filler mixed solution, and freeze-drying to obtain a modified filler;
[0107] The silica nanoparticles are dispersed in ethanol and stirred to obtain a silica nanoparticle dispersion, stearic acid is added thereto, wherein the mass fraction of stearic acid in ethanol is 3 wt.%, and the mass ratio of the silica nanoparticles to stearic acid is 18:1, and the reaction is carried out at a constant temperature of 78° C. for 4 hours, and then filtered, washed, and dried to obtain modified silica nanoparticles;
[0108] 80 parts of polybutylene succinate and 8 parts of modified silica nanoparticles were mixed under stirring, and then 20 parts of modified fillers, 1 part of polyethylene glycol, and 1 part of antioxidant 1010 were added and stirred to obtain a waterproof functional layer substrate, which was added to a twin-screw extruder for melt blending, wherein the melt blending temperature was 190° C., the time was 20 minutes, and the screw speed was 100 rpm. The obtained melt blend was cast into a film and then heat-cured to obtain a waterproof functional layer 3;
[0109] S3: using perfluorooctyl triethoxysilane to modify a polyurethane prepolymer to obtain a modified polyurethane; using palmitic acid to modify a reflective material to obtain a fatty acid-coated reflective material; mixing a fluorinated polyurethane and an organic silicone resin, and then sequentially adding a fatty acid-coated reflective material, an ultraviolet absorber, and a hydrophobic modifier and mixing them evenly to obtain a surface protective layer coating;
[0110] Specifically, S3: dispersing perfluorooctyltriethoxysilane in anhydrous ethanol at a mass fraction of 5wt.%, adding deionized water, wherein the mass ratio of anhydrous ethanol to deionized water is 95:5, adding acetic acid to adjust the pH to 4.5, stirring to obtain a fluorinated silane solution; dispersing a polyurethane prepolymer in anhydrous toluene, wherein the mass fraction of the polyurethane prepolymer in anhydrous ethanol is 15wt.%, adding a fluorinated silane solution, wherein the mass ratio of perfluorooctyltriethoxysilane to the polyurethane prepolymer is 1:10, adding triethylamine at a molar ratio of 1.5:1 to perfluorooctyltriethoxysilane, reacting at a constant temperature of 60°C for 2h to obtain a reaction solution C, and rotary evaporating to obtain a modified polyurethane;
[0111] Dissolve palmitic acid in anhydrous ethanol to obtain a palmitic acid solution with a concentration of 0.1 mol / L, add titanium dioxide to the palmitic acid solution, wherein the mass ratio of titanium dioxide to the palmitic acid solution is 1:15, stir and react at 58° C. for 2 h, filter, wash, and dry to obtain a fatty acid-coated reflective material;
[0112] 60 parts of fluorinated polyurethane and 30 parts of silicone resin were mixed, and 15 parts of fatty acid coated reflective material, 0.5 parts of antioxidant 1010, 0.5 parts of ultraviolet absorber UV-328, and 3 parts of sodium stearate were added in sequence and stirred to obtain a surface protective layer coating 4;
[0113] S4: Clean the contact surfaces of the reinforcement layer 2 and the waterproof functional layer 3, and stack them, and place them in a hot press for compounding, wherein the temperature of the hot press compounding is 150°C, the pressure is 5 MPa, and the time is 20 minutes. After completion, keep the pressed state and naturally cool to room temperature to obtain a composite material, apply the surface protective layer coating 4 on the surface 3 of the waterproof functional layer, and bake and cure at 100°C for 30 minutes to obtain an environmentally friendly biodegradable waterproof membrane.
[0114] Example 3
[0115] This embodiment provides an environmentally friendly biodegradable waterproof coiled material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0116] S1: Pre-treating the bio-based fiber and the natural fiber and dispersing them in a binder solution to obtain a mixed solution A, adding a hydrophobic modifier to obtain a mixed solution B, ultrasonically dispersing and stirring to obtain a slurry, and obtaining a reinforcement layer through a wet molding process;
[0117] Specifically, S1: 50 parts of polylactic acid fiber and 35 parts of flax fiber were sheared, washed and dried to obtain pretreated fiber; 15 parts of polyvinyl alcohol were dispersed in deionized water to obtain a polyvinyl alcohol solution with a concentration of 0.18 g / mL; the pretreated fiber was added to the polyvinyl alcohol and starch glue solution to obtain a mixed solution A, and 10 parts of zinc stearate were added to obtain a mixed solution B after stirring the mixture at a stirring speed of 1000 rpm for 30 minutes, and ultrasonic dispersion and stirring were performed to obtain a slurry, wherein the ultrasonic dispersion power was 270 W, the time was 20 minutes, the stirring temperature was 50°C, and the time was 18 minutes, the slurry was poured onto the forming mesh of the wet papermaking equipment, a vacuum filtration device was used to form a wet fiber web, and the web was placed in a hot press to obtain a preliminary reinforcement layer, wherein the hot pressing temperature was 150°C, the pressure was 7.5 MPa, and the time was 10 minutes, and the reinforcement layer 2 was obtained after drying;
[0118] S2: dispersing montmorillonite and bentonite in a bio-based cationic surfactant solution to obtain a modified mixed filler, adding the mixed filler to a regenerated cellulose solution, and adding polyvinyl pyrrolidone to obtain a modified filler; dispersing silica nanoparticles in a stearic acid ethanol solution to obtain modified silica nanoparticles;
[0119] The bio-based polymer, modified silica nanoparticles, modified fillers, toughening agents, and antioxidants are mixed, melt-blended, cast, and then thermally cured to obtain a waterproof functional layer;
[0120] Specifically, S2: dispersing montmorillonite and bentonite in a betaine solution with a mass fraction of 3.5wt.% at a mass ratio of 1.8:1, wherein the total mass ratio of betaine to montmorillonite and bentonite is 1:25, stirring and reacting at 57°C for 20 minutes, filtering, washing and drying after the reaction to obtain a modified mixed filler, adding the modified mixed filler to a regenerated cellulose solution with a mass fraction of 8.8wt.%, wherein the mass ratio of the modified mixed filler to the regenerated cellulose is 10:1, and then adding polyvinyl pyrrolidone in an amount of 4.6wt.% of the regenerated cellulose, ultrasonically dispersing to obtain a filler mixed solution, and freeze-drying to obtain a modified filler;
[0121] The silica nanoparticles are dispersed in ethanol and stirred to obtain a silica nanoparticle dispersion, stearic acid is added thereto, wherein the mass fraction of stearic acid in ethanol is 4.4 wt.%, and the mass ratio of the silica nanoparticles to the stearic acid is 15:1, and the reaction is carried out at a constant temperature of 80° C. for 3.5 hours, and then filtered, washed, and dried to obtain modified silica nanoparticles;
[0122] 60 parts of polylactic acid and 12 parts of modified silica nanoparticles were mixed under stirring, and then 30 parts of modified filler, 5 parts of glycerol and 3 parts of antioxidant 1076 were added and stirred to obtain a waterproof functional layer substrate, which was added to a twin-screw extruder for melt blending, wherein the melt blending temperature was 170° C., the time was 12 min, and the screw speed was 150 rpm. The obtained melt blend was cast into a film and then heat-cured to obtain a waterproof functional layer 3;
[0123] S3: using perfluorooctyl triethoxysilane to modify a polyurethane prepolymer to obtain a modified polyurethane; using palmitic acid to modify a reflective material to obtain a fatty acid-coated reflective material; mixing a fluorinated polyurethane and an organic silicone resin, and then sequentially adding a fatty acid-coated reflective material, an ultraviolet absorber, and a hydrophobic modifier and mixing them evenly to obtain a surface protective layer coating;
[0124] Specifically, S3: dispersing perfluorooctyl triethoxysilane in anhydrous ethanol with a mass fraction of 7.5wt.%, adding deionized water, wherein the mass ratio of anhydrous ethanol to deionized water is 92:8, adding acetic acid to adjust the pH to 5, stirring to obtain a fluorinated silane solution; dispersing a polyurethane prepolymer in anhydrous toluene, wherein the mass fraction of the polyurethane prepolymer in anhydrous ethanol is 13.8wt.%, adding a fluorinated silane solution, wherein the mass ratio of perfluorooctyl triethoxysilane to the polyurethane prepolymer is 1:5, adding triethylamine in a molar ratio of 1.25:1 to perfluorooctyl triethoxysilane, reacting at a constant temperature of 70°C for 1h to obtain a reaction solution C, and rotary evaporating to obtain a modified polyurethane;
[0125] Dissolve palmitic acid in anhydrous ethanol to obtain a palmitic acid solution with a concentration of 0.34 mol / L, add zinc oxide to the palmitic acid solution, wherein the mass ratio of zinc oxide to the palmitic acid solution is 1:10, stir and react at 50° C. for 2.8 h, filter, wash, and dry to obtain a fatty acid-coated reflective material;
[0126] 40 parts of fluorinated polyurethane and 10 parts of silicone resin were mixed, and after stirring and mixing, 5 parts of fatty acid coated reflective material, 2 parts of antioxidant 1076, 2 parts of ultraviolet absorber UV-327, and 0.5 parts of zinc stearate were added in sequence and stirred and mixed to obtain a surface protective layer coating 4;
[0127] S4: Clean the contact surfaces of the reinforcement layer 2 and the waterproof functional layer 3, overlap them, and place them in a hot press for compounding, wherein the temperature of the hot press compounding is 180°C, the pressure is 8.8 MPa, and the time is 18 minutes. After completion, keep the pressed state and naturally cool to room temperature to obtain a composite material, apply the surface protective layer coating 4 on the surface 3 of the waterproof functional layer, and bake and cure at 80°C for 20 minutes to obtain an environmentally friendly biodegradable waterproof membrane.
[0128] Example 4
[0129] This embodiment provides an environmentally friendly biodegradable waterproof coiled material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0130] S1: Pre-treating the bio-based fiber and the natural fiber and dispersing them in a binder solution to obtain a mixed solution A, adding a hydrophobic modifier to obtain a mixed solution B, ultrasonically dispersing and stirring to obtain a slurry, and obtaining a reinforcement layer through a wet molding process;
[0131] Specifically, S1: 48 parts of polyhydroxy fatty acid fibers and 37 parts of bamboo fibers were sheared, washed, and dried to obtain pretreated fibers; 22 parts of starch glue were dispersed in deionized water to obtain a starch glue solution with a concentration of 0.2 g / mL; the pretreated fibers were added to the starch glue solution to obtain a mixed solution A, and 8.6 parts of sodium stearate and zinc stearate were added to obtain a mixed solution B after stirring the reaction at a stirring speed of 920 rpm and a time of 24 min, and ultrasonic dispersion and stirring were performed to obtain a slurry, wherein the ultrasonic dispersion power was 300 W, the time was 18 min, the stirring temperature was 47° C., and the time was 20 min, the slurry was poured onto a forming mesh cloth of a wet papermaking equipment, a vacuum filtration device was used to form a wet fiber web, and the web was placed in a hot press to obtain a preliminary reinforcement layer, wherein the hot pressing temperature was 172° C., the pressure was 10 MPa, and the time was 14 min, and the reinforcement layer 2 was obtained after drying;
[0132] S2: dispersing montmorillonite and bentonite in a bio-based cationic surfactant solution to obtain a modified mixed filler, adding the mixed filler to a regenerated cellulose solution, and adding polyvinyl pyrrolidone to obtain a modified filler; dispersing silica nanoparticles in a stearic acid ethanol solution to obtain modified silica nanoparticles;
[0133] The bio-based polymer, modified silica nanoparticles, modified fillers, toughening agents, and antioxidants are mixed, melt-blended, cast, and then thermally cured to obtain a waterproof functional layer;
[0134] Specifically, S2: dispersing montmorillonite and bentonite in a mass ratio of 2:1 in a lauramide propyl betaine solution with a mass fraction of 4.2wt.%, wherein the total mass ratio of lauramide propyl betaine to montmorillonite and bentonite is 1:22, stirring and reacting at 60°C for 28min, filtering, washing and drying after the reaction to obtain a modified mixed filler, adding the modified mixed filler to a regenerated cellulose solution with a mass fraction of 10wt.%, wherein the mass ratio of the modified mixed filler to the regenerated cellulose is 7.5:1, and then adding polyvinyl pyrrolidone in an amount of 5wt.% of the regenerated cellulose, ultrasonically dispersing to obtain a filler mixed solution, and freeze-drying to obtain a modified filler;
[0135] The silica nanoparticles are dispersed in ethanol and stirred to obtain a silica nanoparticle dispersion, stearic acid is added thereto, wherein the mass fraction of stearic acid in ethanol is 5 wt.%, and the mass ratio of the silica nanoparticles to stearic acid is 20:1, and the reaction is carried out at a constant temperature of 72° C. for 3.8 hours, and then filtered, washed, and dried to obtain modified silica nanoparticles;
[0136] 74 parts of polybutylene succinate and 15 parts of modified silica nanoparticles were mixed under stirring, and then 28 parts of modified filler, 4.2 parts of polyethylene glycol, 2 parts of antioxidant 1010 and antioxidant 1076 were added and stirred to obtain a waterproof functional layer substrate, which was added to a twin-screw extruder for melt blending, wherein the melt blending temperature was 187° C., the time was 10 min, and the screw speed was 200 rpm. The obtained melt blend was cast into a film and then heat-cured to obtain a waterproof functional layer 3;
[0137] S3: using perfluorooctyl triethoxysilane to modify a polyurethane prepolymer to obtain a modified polyurethane; using palmitic acid to modify a reflective material to obtain a fatty acid-coated reflective material; mixing a fluorinated polyurethane and an organic silicone resin, and then sequentially adding a fatty acid-coated reflective material, an ultraviolet absorber, and a hydrophobic modifier and mixing them evenly to obtain a surface protective layer coating;
[0138] Specifically, S3: Disperse perfluorooctyl triethoxysilane in anhydrous ethanol at a mass fraction of 10 wt.%, add deionized water, wherein the mass ratio of anhydrous ethanol to deionized water is 93:7, add acetic acid to adjust the pH to 4.8, and stir to obtain a fluorinated silane solution; disperse a polyurethane prepolymer in anhydrous toluene, wherein the mass fraction of the polyurethane prepolymer in anhydrous ethanol is 10 wt.%, add a fluorinated silane solution, wherein the mass ratio of perfluorooctyl triethoxysilane to the polyurethane prepolymer is 1:7.4, add triethylamine in a molar ratio of 1.35:1 to perfluorooctyl triethoxysilane, react at a constant temperature of 67°C for 1.2 h to obtain a reaction solution C, and rotary evaporate to obtain a modified polyurethane;
[0139] Dissolve palmitic acid in anhydrous ethanol to obtain a palmitic acid solution with a concentration of 0.5 mol / L, add titanium dioxide and zinc oxide to the palmitic acid solution, wherein the mass ratio of titanium dioxide, zinc oxide to the palmitic acid solution is 1:17, stir and react at 60° C. for 4 h, filter, wash and dry to obtain a fatty acid-coated reflective material;
[0140] 55 parts of fluorinated polyurethane and 32 parts of silicone resin were mixed, and after stirring and mixing, 20 parts of fatty acid coated reflective material, 1.2 parts of antioxidant 1010, antioxidant 1076, 1.8 parts of ultraviolet absorber UV-531, 1.8 parts of sodium stearate, and zinc stearate were added in sequence and stirred and mixed to obtain a surface protective layer coating 4;
[0141] S4: Clean the contact surfaces of the reinforcement layer 2 and the waterproof functional layer 3, and stack them, and place them in a hot press for compounding, wherein the temperature of the hot press compounding is 175°C, the pressure is 10MPa, and the time is 10min. After completion, keep the pressed state and naturally cool to room temperature to obtain a composite material, apply the surface protective layer coating 4 on the surface 3 of the waterproof functional layer, and bake and cure at 95°C for 28min to obtain an environmentally friendly biodegradable waterproof membrane.
[0142] Comparative Example 1
[0143] This comparative example provides an environmentally friendly biodegradable waterproof membrane, which is different from Example 1 in that in step S2, the weight portion of the modified silicon dioxide nanoparticles is 20 parts, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0144] Comparative Example 2
[0145] This comparative example provides an environmentally friendly biodegradable waterproof membrane, which is different from Example 1 in that in step S2, the weight portion of modified silicon dioxide nanoparticles is 2 parts, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0146] Comparative Example 3
[0147] This comparative example provides an environmentally friendly biodegradable waterproof membrane, which is different from Example 1 in that in step S2, the weight portion of the modified filler is 35 parts, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0148] Comparative Example 4
[0149] This comparative example provides an environmentally friendly biodegradable waterproof membrane, which is different from Example 1 in that in step S2, the weight portion of the modified filler is 15 parts, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0150] The performance test of the environmentally friendly biodegradable waterproof membranes of the above-mentioned Examples 1-4 and Comparative Examples 1-4 was carried out, and the specific process is as follows:
[0151] Test the samples according to GB / T 328.1-2007 Test methods for building waterproof membranes;
[0152] The test results are shown in Table 1.
[0153] Table 1: Test results of environmentally friendly biodegradable waterproof membrane performance of Examples 1-4 and Comparative Examples 1-4
[0154]
[0155] It can be seen from Table 1 that the environmentally friendly biodegradable waterproof membranes prepared in Examples 1-4 provided by the present invention have good waterproof performance and mechanical properties.
[0156] From the test results of Example 1 and Comparative Examples 1 and 2, it can be seen that when the amount of modified silica nanoparticles added is too much, it is easy to disperse unevenly, increase local stress concentration, and thus cause the flexibility of the functional layer to decrease, causing the coil to crack easily, affecting the service life; when the amount added is too little, the mechanical strength and hydrophobicity of the waterproof layer may be reduced, resulting in an increased risk of moisture penetration, and at the same time, the weather resistance deteriorates, which shortens the life of the coil.
[0157] It can be seen from the test results of Example 1 and Comparative Examples 3 and 4 that when the amount of modified filler added is too much, the viscosity of the system will be too high, affecting the processing performance, and the filler and the polymer matrix interface will be poorly bonded, thereby reducing the overall strength and toughness, resulting in increased brittleness and easy cracking of the coil; when the amount added is too little, the hydrophobicity and weather resistance of the functional layer will decrease, resulting in insufficient performance of the coil.
[0158] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. An environmentally friendly biodegradable waterproofing membrane, characterized in that: It comprises a reinforcing layer, a waterproof functional layer and a surface protective layer; wherein the reinforcing layer, the waterproof functional layer and the surface protective layer are stacked in sequence; The reinforcement layer includes bio-based fibers, natural fibers, a binder, and a hydrophobic modifier; The waterproof functional layer comprises a bio-based polymer, modified silica nanoparticles, a modified filler, a toughening agent and an antioxidant; The surface protection layer comprises fluorinated polyurethane, silicone resin, fatty acid-coated reflective material, antioxidant, ultraviolet absorber and hydrophobic modifier.
2. The environmentally friendly biodegradable waterproofing membrane according to claim 1, characterized in that: The reinforcing layer comprises the following components in parts by weight: The bio-based fiber is polylactic acid fiber or polyhydroxyalkanoic acid fiber; The natural fiber is flax fiber or bamboo fiber; The binder is polyvinyl alcohol or starch glue; The hydrophobic modifier is any one of stearic acid, sodium stearate, and zinc stearate, or a combination of at least two of them.
3. The environmentally friendly biodegradable waterproofing membrane according to claim 1, characterized in that: The waterproof functional layer comprises the following components in parts by weight: The bio-based polymer is polylactic acid or polybutylene succinate; The modified filler is modified montmorillonite, modified bentonite and regenerated cellulose; The toughening agent is glycerol or polyethylene glycol; The antioxidant is any one of vitamin E, antioxidant 1010, antioxidant 1076, or a combination of at least two of them.
4. The environmentally friendly biodegradable waterproofing membrane according to claim 1, characterized in that: The surface protective layer comprises the following components in parts by weight: The reflective material in the fatty acid-coated reflective material is any one of zirconium oxide, titanium dioxide, and zinc oxide, or a combination of at least two thereof; The ultraviolet absorber is any one of ultraviolet absorber UV-326, ultraviolet absorber UV-328, ultraviolet absorber UV-327, and ultraviolet absorber UV-531, or a combination of at least two thereof.
5. A method for preparing an environmentally friendly biodegradable waterproofing membrane according to any one of claims 1 to 4, characterized in that: The preparation method comprises: S1: Pre-treating the bio-based fiber and the natural fiber and dispersing them in a binder solution to obtain a mixed solution A, adding a hydrophobic modifier to obtain a mixed solution B, ultrasonically dispersing and stirring to obtain a slurry, and obtaining a reinforcement layer through a wet molding process; S2: dispersing montmorillonite and bentonite in a bio-based cationic surfactant solution to obtain a modified mixed filler, adding the mixed filler to a regenerated cellulose solution, and adding polyvinyl pyrrolidone to obtain a modified filler; dispersing silica nanoparticles in a stearic acid ethanol solution to obtain modified silica nanoparticles; The bio-based polymer, modified silica nanoparticles, modified fillers, toughening agents, and antioxidants are mixed, melt-blended, cast, and then thermally cured to obtain a waterproof functional layer; S3: using perfluorooctyl triethoxysilane to modify a polyurethane prepolymer to obtain a modified polyurethane; using palmitic acid to modify a reflective material to obtain a fatty acid-coated reflective material; mixing a fluorinated polyurethane and an organic silicone resin, and then sequentially adding a fatty acid-coated reflective material, an ultraviolet absorber, and a hydrophobic modifier and mixing them evenly to obtain a surface protective layer coating; S4: Clean the contact surfaces of the reinforcement layer and the waterproof functional layer, stack them, place them in a hot press for compounding, keep them in the pressed state and naturally cool them to room temperature to obtain a composite material, apply a surface protective layer coating on the surface of the waterproof functional layer, and bake and cure them to obtain an environmentally friendly biodegradable waterproof membrane.
6. The method for preparing an environmentally friendly biodegradable waterproofing membrane according to claim 5, characterized in that: In S1: the concentration of the binder is 0.1-0.2 g / mL.
7. The method for preparing an environmentally friendly biodegradable waterproofing membrane according to claim 5, characterized in that: In S2: The mass ratio of montmorillonite to bentonite is (1-2):1; The bio-based cationic surfactant is betaine or lauramidopropyl betaine; The mass fraction of the bio-based cationic surfactant solution is 2-5wt.%; The total mass ratio of the bio-based cationic surfactant to montmorillonite and bentonite is 1:(15-25); The mass ratio of the modified mixed filler to the regenerated cellulose is (5-10):1; The mass fraction of the regenerated cellulose solution is 5-10wt.%; The feeding amount of the polyvinyl pyrrolidone accounts for 2-5wt.% of the regenerated cellulose.
8. The method for preparing an environmentally friendly biodegradable waterproofing membrane according to claim 5, characterized in that: In S2: the mass ratio of the silicon dioxide nanoparticles to stearic acid is (10-20): 1; The mass fraction of the stearic acid ethanol solution is 1-5wt.%.
9. The method for preparing an environmentally friendly biodegradable waterproofing membrane according to claim 5, characterized in that: In S3: The mass ratio of the perfluorooctyltriethoxysilane to the polyurethane prepolymer is 1:(5-10); The concentration of the palmitic acid solution is 0.1-0.5 mol / L; The mass ratio of the reflective material to the palmitic acid solution is 1:(10-20).
10. The method for preparing an environmentally friendly biodegradable waterproofing membrane according to claim 5, characterized in that: In S4: The temperature at which the reinforcing layer and the waterproof functional layer are compounded in the hot press is 150-180°C; The pressure of the reinforcing layer and the waterproof functional layer in the hot press is 5-10MPa; The time for compounding the reinforcing layer and the waterproof functional layer in the hot press is 10-20 minutes; The baking and curing temperature is 80-100°C; The baking and curing time is 20-30 minutes.
Citation Information
Patent Citations
Water-based superhydrophobic coating and preparation method thereof
CN108893052A
Wet preparation method of cotton stalk fiber non-woven fabric
CN111593600A
Semi-coated super-hydrophobic quartz sand proppant and preparation method thereof
CN118995191A
Environment-friendly bio-based nano reinforced waterproof material as well as preparation method and application thereof
CN119119596A
Cited By
Method and matched device for preventing fruit tree from fruit cracking
CN120513803A